PENYELESAIAN SENGKETA PENERIMA WARALABA DALAM PERJANJIAN WARALABA ANTARA CV. HUTAMA MANDIRI JAYA DAN PT. INDOMARCO PRISMATAMA (STUDI KASUS PUTUSAN NO. 204/Pdt.G/2021/PN Bdg) - Hendra Kurniawan; Rumainur (INTELIGENSIA MEDIA, 2025)
The development of franchise businesses has grown rapidly and has become a new force for the domestic economic sector in Indonesia. One example of a franchise business that is in great demand is the minimarket franchise business. PT. Indomarco Pristama is the franchise right holder for the